UBUNGAN SIKAP IBU DENGAN PEMBERIAN ASI ESKLUSIF DI POSYANDU CUT NYA’DIEN DAN POSYANDU DEWI SARTIKA DESA BANYUPUTIH KIDUL - Isnaini Isnaini; Muthmainah Zakiyyah; Sri Wahyuningsih (NHM PRESS, 2023)
Breastfeeding is a natural process, but mothers often fail to breastfeed or stop breastfeeding when they should. The success of exclusive breastfeeding is influenced by several factors, one of which is the attitude of the mother. Based on Basic Health Research (RISKESDAS) 2021 data, 52.5 percent or only half of the 2.3 million babies aged less than six months are exclusively breastfed in Indonesia, or a decrease of 12 percent from the 2019 rate. The rate of early initiation of breastfeeding (IMD) also decreased from 58.2 percent in 2019 to 48.6 percent in 2021. In the initial study conducted, data on exclusive breastfeeding only reached 60.98%, that is, out of 33 respondents there were 18 mothers who did not provide exclusive breastfeeding to their babies. This type of research is was analytic survey research using a cross-sectional approach/design .the total population was 100 mother respondents who have babies aged 0-12 months. Data collection used a questionnaire. The Analysis used univariate, and bivariate with Chie Square test. from the Asymp value . Sig The Chi Square test is 0.000 and the chie square is squared with a significance of α = 0.05 which means the Asymp value. Sig Chie-Square 0.000 <0.05, then it can be concluded that Ho is rejected and Ha is accepted, which means there is a relationship between the mother's attitude and exclusive breastfeeding at Posyandu Cut Nya'dien and Posyandu Dewi Sartika Banyuputih Kidul Village in 2023 . From the results of this study there are still some mothers who have a negative attitude towards exclusive breastfeeding so that education or counseling is still needed to be given to mothers to increase knowledge so that the mother's attitude can be positive.